Analisis Rasio Keuangan dan Kaitannya dengan Kinerja Keuangan Perusahaan - Abdi Maliki; Ruhiat (Asosiasi Ahli Administrasi Indonesia, 2020)
The aim of this study is to determine the effects of financial ratio analysis in assessing the performance of transportation companies. The samples of this study are the transportation companies of the 2010-2012 period that are registered on Indonesia’s stock exchange. The data are analyzed using multiple linear regression. The result of the study shows that variable changes in financial ratios Debt to Assets Ratio and Debt to Equity Ratio have a significant effect on changes in ROE. However, changes in financial ratios current ratio, total asset turn ratio, return on investment, and earnings per share have no significant effect on changes in earnings After Tax.